CRISPR-Cas12a-Assisted Genome Editing in Amycolatopsis mediterranei - Zhou, Yajuan; Liu, Xinqiang; Wu, Jiacheng; Zhao, Guoping; Wang, Jin (Frontiers in Bioengineering and Biotechnology, 2020)
Amycolatopsis mediterranei U32 is an industrial producer of rifamycin SV, whose derivatives have long been the first-line antimycobacterial drugs. In order to perform genetic modification in this important industrial strain, a lot of efforts have been made in the past decades and a homologous recombination-based method was successfully developed in our laboratory, which, however, requires the employment of an antibiotic resistance gene for positive selection and did not support convenient markerless gene deletion. Here in this study, the clustered regularly interspaced short palindromic repeat (CRISPR) system was employed to establish a genome editing system in A. mediterranei U32. Specifically, the Francisella tularensis subsp. novicida Cas12a (FnCas12a) gene was first integrated into the U32 genome to generate target-specific double-stranded DNA (dsDNA) breaks (DSBs) under the guidance of CRISPR RNAs (crRNAs). Then, the DSBs could be repaired by either the non-homologous DNA end-joining (NHEJ) system or the homology-directed repair (HDR) pathway, generating inaccurate or accurate mutations in target genes, respectively. Besides of A. mediterranei, the present work may also shed light on the development of CRISPR-assisted genome editing systems in other species of the Amycolatopsis genus.